Assessing the shoreline changes in Tra Vinh provinceusing multi-temporal remote sensing data - Tran Ha Phuong,; Hoang Phi Phung,; Nguyen Thanh Hung,; Hoang Cong Tri, (Vietnam Journal of Science and Technology, 2018)
The erosion – deposition of shore line is not only a natural phenomenon, but also influenced by human activities. In recent decades, these changes occur more frequently with changes in the shape of shoreline, the change in area of coastal mangroves as well as loss of productive land. In the trend of sea level rise, a study on changes of estuaries is necessary, in order to preserve and develop the mangroves, disposition, production planning infrastructure and civil works, ...By using multi – temporal remote sensing from 1989 to 2015 and techniques appropriate digital image processing. The changes of erosion – deposition in shoreline are determined and contributed to clarify of erosion – deposition rules of the Mekong Delta. The results show that the shoreline of Tra Vinh province has changed over the years. This change is concentrated in some points such as: erosion occurs strongly in Hiep Thanh Commune, Long Thanh and Dan Thanh Communes with erosion rate can reach to 13 - 15 m per year. In addition, the deposition occurs mainly in communes such as My Long Nam commune, the first half of Truong Long Hoa and the area of Dong Hai and Long Vinh communes. The shoreline forecast for 2015 and 2017 is made for the entire shoreline of Tra Vinh province. The forecasted results show the trend of coastal deposition and erosion in the coming years, especially in the shoreline areas with strong changes as mentioned above. The phenomenon of erosion is predicted in the communes of Hiep Thanh, Long Hoa and Dan Thanh in the following years.